1979
DOI: 10.1038/bjc.1979.68
|View full text |Cite
|
Sign up to set email alerts
|

Response of the rat to saccharin with particular reference to the urinary bladder

Abstract: Summary.-Male and female Wistar rats were administered sodium saccharin for life (2 yr) either in the drinking water or diet. The maximum palatable dose of saccharin in the drinking water was found to be 2 g/kg/day and, even then, there was some voluntary restriction of fluid intake in the males. By contrast, double this dose -namely 4 g/kg/day, was palatable in the diet. A control group of rats of both sexes received saccharin-free diet and drinking water. Mild urothelial hyperplasias developed from 85 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…A few hyperplasias in control Wistar males (but not females) were recorded in previous experiments from this laboratory (Chowaniec & Hicks, 1979).…”
Section: Electron Microscopymentioning
confidence: 51%
See 1 more Smart Citation
“…A few hyperplasias in control Wistar males (but not females) were recorded in previous experiments from this laboratory (Chowaniec & Hicks, 1979).…”
Section: Electron Microscopymentioning
confidence: 51%
“…22). DISCUSSION MNU has a short (5-10 min) half-life in the body (Swann, 1968), but its rate of decay is pH-dependent, and at the normal pH of rat urine (6.0-6.5; Chowaniec & Hicks, 1979) it will persist much longer. Using tritiated MNU and high-pressure liquid chromatography, we had previously demonstrated the half-life of MNU in Hanks' balanced salt solution to be -300 min at pH 6-0, 150 min at pH 6-3 and 90 min at pH 6-5 (Knowles, Moore and Hicks, umpublished).…”
Section: Electron Microscopymentioning
confidence: 98%
“…Relatively more (47%) of the free N-hydroxy derivative is found if the urine of the treated rats is made acidic (pH 5 7 + 0.3) than if it is made alkaline (pH 7 7 + 0.2), when only 29% is in the form of the free N-hydroxy compound (Kadlubar et al, 1978). These authors suggested that urinary pH is the controlling factor in 2-naphthylamine- (Chowaniec & Hicks, 1979) is slightly lower than that found by Kadlubar and his colleagues. By comparison with the relatively low doses of MNU, BBN and FANFT required to produce bladder cancer in the rat, a very high dose of 2-naphthylamine was used here to produce less than a 100% incidence.…”
Section: Discussionmentioning
confidence: 79%
“…Saccharin is not mutagenic but, like MMS, does cause sister chromatid exchange (Albe and Sakaki, 1977;Wolff and Rodin, 1978). If a genetic event of this sort which is not a new mutation can result in tumour formation, this is evidence per se either that the rat urothelium carries a latent oncogene, or as we have suggested elsewhere (Chowaniec and Hicks, 1979), that most animal populations are exposed to low levels of undetected environmental initiating carcinogens.…”
Section: Discussionmentioning
confidence: 97%